Photo sensors increase likelihood of detection of expelled vaginal implant transmitters - Michael J. Cherry; Melinda A. Nelson; Robert J. Warren; L. Mike Conner (Wildlife Society Bulletin)
ABSTRACT Vaginal implant transmitters (VITs) are small radiotransmitters implanted in the vaginal canal of adult female ungulates following the breeding season. Immediately prior to parturition, the VIT is expelled and a temperature sensor causes the pulse rate to change from 40 pulses/minute to 80 pulses/minute, thereby indicating a parturition event to researchers. Climatic conditions can affect the performance of VITs; therefore, in collaboration with Advanced Telemetry Systems, we developed and evaluated a VIT equipped with both temperature and photo sensors. We used publicly available data on ambient temperature and daylight during June–August 2011 (i.e., the generalized ungulate parturition season) for 35 sites across the United States to predict improvement in performance achieved by the inclusion of a photo sensor. Mean predicted improvement below the 40th and 35th parallel of latitude is 33% and 43%, respectively. Unlike the temperature sensor, the photo sensor activates immediately when ambient light is ≥0.01 lux, improving the resolution of temporal parturition data and associated neonate search protocols. © 2013 The Authors. Wildlife Society Bulletin published by Wiley Periodicals, Inc. on behalf of The Wildlife Society